2015
DOI: 10.1111/pde.12615
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Lichen Sclerosus: A Review of the Epidemiology and Treatment Options

Abstract: Lichen sclerosus (LS) is a rare, chronic, inflammatory disease of the skin that primarily affects postmenopausal women but may occur in men and children as well. Approximately 7% to 15% of cases are believed to occur in children. The epidemiologic data for LS have been limited and treatment options are not well studied, particularly in children. We reviewed new developments available in the current literature on the epidemiology and management of LS for children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 63 publications
0
41
0
4
Order By: Relevance
“…Medical treatment can be considered as additional to circumcision and used postoperatively to prevent or reduce complications. In a pediatric age, a study of 36 girl patients affected by LS and treated with high corticosteroid doses showed that 75% of patients had full remission after treatment and only 25% a partial response to treatment, while a study of 40 male children affected by LS showed clinical improvement in 40% [ 6 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Medical treatment can be considered as additional to circumcision and used postoperatively to prevent or reduce complications. In a pediatric age, a study of 36 girl patients affected by LS and treated with high corticosteroid doses showed that 75% of patients had full remission after treatment and only 25% a partial response to treatment, while a study of 40 male children affected by LS showed clinical improvement in 40% [ 6 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Circumcision is the treatment of choice, but topical use of several drugs has been used before or after surgical treatment [ 6 ]. The British Association of Dermatologists guideline recommends the treatment of patients affected by BXO with a highly potent corticosteroid [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lichen sclerosus (LS) (synonym: Lichen sclerosus et atriphicans ) is not as common in childhood when compared with adults; however 7%‐15% of cases are believed to occur in children …”
Section: Autoimmune and Diseases Of Unknown Causementioning
confidence: 99%
“…22 In the diaper area, pruritus (itchiness) is the most common complaint, while perianal lesions may cause painful defecation and constipation. Although there may be an increased risk of leukoplakia and squamous cell carcinoma in adults, this is not the case in children.…”
Section: Additional Types Of Inflammatory Dermatosesmentioning
confidence: 99%
“…Although there may be an increased risk of leukoplakia and squamous cell carcinoma in adults, this is not the case in children. 22 Symptoms of Crohn's disease, a type of inflammatory bowel disease that is rare among infants, can manifest in the diaper area. Perianal fissuring (painful tear or crack) and ulcerations (open sores of the skin) as well as persistent papules, nodules, plaques, and woody induration (becoming firm or tense) of the vulvar and scrotal skin should trigger an evaluation for Crohn's disease, particularly in the distal colon.…”
Section: Additional Types Of Inflammatory Dermatosesmentioning
confidence: 99%